2021
DOI: 10.1007/s10964-021-01434-y
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Interplay between Ethnic, National, and Personal Identity in Immigrant Adolescents

Abstract: Developing a personal identity is a core developmental task for all adolescents. Immigrant adolescents need to integrate the meaning that their belonging to their ethnic group and the receiving nation has for them into their personal identity. The purpose of this study was to examine the longitudinal interplay between personal, ethnic, and national identities of a middle school sample of immigrant youth (N = 765, Mage = 12.7 years, SD = 0.6 at T1; 46% girls) enroled in Greek schools. Data were collected in thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 48 publications
2
13
0
Order By: Relevance
“…It might be further triggered by experiencing relatively greater acculturative stress fueled by the perceived pressure to maintain and adopt components of both one’s heritage and destination cultures (Schwartz & Zamboanga, 2008). Notably, cultural identity confusion could be intertwined with confusion in personal identities as well (Mastrotheodoros et al, 2021; Meca et al, 2017). Therefore, youth in the marginalized identity profile may be at high risk of experiencing difficulties in the formation of their self and personality.…”
Section: Discussionmentioning
confidence: 99%
“…It might be further triggered by experiencing relatively greater acculturative stress fueled by the perceived pressure to maintain and adopt components of both one’s heritage and destination cultures (Schwartz & Zamboanga, 2008). Notably, cultural identity confusion could be intertwined with confusion in personal identities as well (Mastrotheodoros et al, 2021; Meca et al, 2017). Therefore, youth in the marginalized identity profile may be at high risk of experiencing difficulties in the formation of their self and personality.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas most previous research focused on native adolescents, some studies have investigated links between family processes and youth identity development in immigrant-origin groups. For example, immigrant-origin adolescents' family functioning was positively associated with ethnic identity belonging (Reitz et al, 2014), which reflects self-processes similar to and linked with identity commitments (Mastrotheodoros et al, 2021). Similarly, parents' ethnic identity belonging facilitated immigrant-origin adolescents' identity development (e.g., Meca et al, 2021), further supporting the role of family dynamics in immigrant-origin youth's identity development.…”
Section: Differences Between Immigrant-origin and Native Adolescentsmentioning
confidence: 77%
“…One study (King et al, 2019 ) only reported validity, reporting the face validity of the CCS-CA. The reported internal consistency was adequate (Cronbach's alpha ≥ 0.70) in all but one study (Mastrotheodoros et al, 2021 ) that reported poor reliability for the MEIM in some time points. The reported and established types of validity in the three studies include construct, convergent, content, and face validity.…”
Section: Resultsmentioning
confidence: 94%